“Efecto de dietas con Spirulina SP contra bacterias patógenas de tipo vibrio en camarón blanco Litopenaeus Vannamei)” - Castellano Araujo, Frank Javier (2021)
The shrimp industry represents one of the most important economic activities worldwide, however; Despite its importance, this industry is affected by the presence of pathogenic bacteria, especially of the Vibrio genus, which cause high mortalities and great economic losses. The objective of this work was to analyze the effect of functional diets with the inclusion of Spirulina sp, against Vibrio-type pathogenic bacteria in white shrimp (Litopenaues vannamei). The research was experimental and was developed at the "La María" University Campus, on the premises of the State Technical University of Quevedo, under a completely randomized design, with 3 treatments (2, 4 and 6% of Spirulina sp. ) and two experimental controls (positive and negative) in triplicate. The vibrios were isolated directly from the shrimp intestine, which were cultured in selective TCBS media until reaching a density of 1x108 CFU bacterial density selected with a previous LC50 experiment. The organisms were fed for 41 days with diets including spirulina and exposed to Vibrios. The results showed that the diet with the highest protection against the pathogenic bacteria of the Vibrio genus was the inclusion of 4% Spirulina sp in the balance, which obtained 47% mortality in shrimp with respect to the positive control (80%) exposed to pathogenic bacteria. Vibrio Type. With these results, benefits are generated to the aquaculture sector because it allows the control and prevention of infections of bacterial origin. Keywords: Functional food, Intestine, Immunosimulant, Spirulina